The Relationship between Parents’ Socio-Economic Level and Parenting with Early Childhood’s Moral Development - Ratna Komalasari, Ratu; Atikah, Cucu; Asmawati, Luluk (Al-Athfal: Jurnal Pendidikan Anak, 2022)
Purpose – The socio-economic status of parents has an impact on parenting for early childhood. The purpose of this study is to explain the relationship between parents’ socio-economic level and parenting with the moral development of early childhood.Design/methods/approach – This quantitative research using a correlation method was carried out in Raudhatul Athfal Al-Izzah Serang City, dealing with 100 parents as the research population. The sampling technique used is simple random sampling with slovin formula as many as 80 people. The data on the variables of parents’ economic level, parenting, and early childhood’s moral development are measured by questionnaires. The data are then analyzed with Pearson Product Moment.Findings – The results of the first hypothesis test show that there is no relationship between parents’ socio-economic level and the moral development of early childhood. The results are indicated by the value of rcount < rtable (0.149 < 0.220) and the significance value of 0.186 > 0.05. Moreover, the results of the second hypothesis test show that there is a relationship between parenting and early childhood’s moral development, justified by the value of rcount > rtable (0.380 > 0.220) and the significance value of 0.000 < 0.05. Finally, the results of the third hypothesis test show that there is a relationship between parents’ socio-economic level, parenting, and the moral development of early childhood. The evidence is indicated by the value of rcount > rtable (0.412 > 0.220) and the significance value of 0.001 < 0.15. Research implications/limitations – This study was limited on two independent variables and one dependent variable. Thus, further studies are expected to be able to explore more using other variables.Practical implications – This quantitative research helps clarify that the socio-economic level and parenting can influence the moral development of early childhood.Originality/value – The high and low socio-economic level of parents does not correlate with the moral development of early childhood. Therefore, it is necessary for parents to understand more or to practice more on parenting that can stimulate the moral development of early childhood and become good figures and role models for early childhood. Paper type Research paper